Tabungan Botol Bekas: Media Literasi Keuangan Anak Usia Dini Berbasis Nilai Ekonomi Hindu - Juliartana, I Putu Gede Kamestya; Sudarma, I Made; Gunada, I Wayan Agus; Yasa, I Komang Widya Purnama (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service program aimed to enhance financial literacy among early childhood children in Dusun Pemangkalan, Batu Mekar Village, through the creation of creative savings from used bottles integrated with Hindu economic values. The methodological approach included community education, participatory training, and demonstration sessions. Activities were conducted through multiple phases: initial socialization about financial literacy importance, creative workshops on transforming waste bottles into functional piggy banks, and the introduction of basic Hindu economic principles such as Tri Hita Karana and the concept of Artha. The results indicated a modest improvement in children's understanding of saving concepts and money values, with pre-intervention assessment showing 35% understanding and post-intervention reaching 55%. Parental involvement was observed to be crucial, though participation levels varied. Environmental awareness also showed slight improvement. The study concludes that while culturally contextual and creative approaches show potential, sustained efforts and longer intervention periods are needed for significant impact. The integration of local values proved meaningful in connecting abstract financial concepts to children's daily experiences.